The Effect of Spindle Speed on The Surface of Teak Wood Work Pieces on A 3 Axis CNC Router Machine : The Effect of Spindle Speed on The Surface of Teak Wood Work Pieces on A 3 Axis CNC Router Machine - nulhakim, lukman (P3M Politeknik Negeri Media Kreatif, 2025)
The effectiveness of machining process time and surface roughness quality are the main factors for evaluating whether the machining product is acceptable or not. Spindle speed is one way to maximize process time. This study aims to determine the effect of spindle speed variations on the surface roughness of objects made of teak wood material using a 3-axis CNC router machine. The research method uses an experimental method on objects made of teak wood using spindle speed variations of 4000, 6000, and 8000 RPM. Then the surface roughness measurements were carried out, and the measurement results were analyzed to determine the effect of spindle speed variations. The results of the study on the surface roughness of objects, spindle speed 8000 RPM produced a Ra value of 10.988 µm which is the lowest Ra value.